Discussion on the application and benefits of job crafting theory in improving occupational stability among newly recruited nurses in Traditional Chinese Medicine hospitals (工作重塑理论赋能中医院新入职护士职业稳定性的机制与优势) - LIU Xin (刘欣); LI Miao (李苗); CHEN Ying (陈迎); CHANG Yuying (常玉莹); NING Shanshan (宁珊珊); GUO Linyu (郭琳宇) (中西医结合护理)
The job crafting theory offers a novel perspective for enhancing occupational stability among newly recruited nurses in Traditional Chinese Medicine hospitals. This paper systematically reviews the definition of job crafting theory, its research tools, and its current applications both domestically and internationally. It further examines specific implementation strategies for newly hired nurses in Traditional Chinese Medicine hospitals, analyzes the theory's positive impact on enhancing occupational stability among this group, and proposes reference for future research, talent training and sustainable development of Chinese medicine nursing. (工作重塑理论为破解中医院新入职护士高离职率难题提供了新的理论视角与实践路径。本研究就工作重塑理论在提升中医院新入职护士职业稳定性中的理论优势与实践潜力进行阐述, 旨在拓宽该理论在护理领域的应用场景, 并为构建可持续的中医护理人才队伍提供循证依据。)